Analisis Pertimbangan Hakim dalam Putusan Pengadilan Negeri Bukittinggi Perkara Narkotika Perspektif Hukum Pidana Islam - Reza Syalsa Billa; Jerry Pratama (Lembaga Yasin AlSys, 2026)
This study was motivated by the existence of a discrepancy between the facts revealed in the trial and the judge’s considerations in the decision on a narcotics crime case at the Bukittinggi District Court Number 118/Pid.Sus/2021/PN BKT, particularly regarding the defendant’s role as both a user and a dealer. This study aims to analyze the judge’s considerations in that decision and to assess their relevance to the concept of jarimah in Islamic criminal law. This study used a normative legal research method with a qualitative approach through an examination of primary legal materials in the form of court decisions, as well as secondary legal materials in the form of statutory regulations, legal literature, and the opinions of ulama regarding narcotics jarimah from the perspective of Islamic criminal law. The results showed that the judge’s considerations in the decision placed greater emphasis on formal juridical aspects by applying the article on narcotics possession, even though the facts revealed in the trial disclosed the defendant’s role as both a narcotics user and dealer. The judge’s decision imposing a lighter sentence than the prosecutor’s demand was considered not to have fully reflected the degree of culpability and the social impact of the defendant’s act. From the perspective of Islamic criminal law, the acts of narcotics abuse and distribution fall under jarimah ta’zir because they damage العقل and endanger society. This study concludes that the Bukittinggi District Court Decision Number 118/Pid.Sus/2021/PN BKT has relevance to the concept of jarimah ta’zir, but the application of its sanction is considered not yet optimal in realizing the objectives of Islamic punishment, namely public benefit, justice, and deterrence.